Character Development Strategy for Santri Through Extracurricular Scouting at the Darussalam Islamic Boarding School, Bogor - Syamsul Rizal Mz; Nabella Lestari (al-Afkar, Journal For Islamic Studies, 2024)
The Scout Movement is an organization that pays great attention to moral issues or the character of students. This study specifically examines the character building carried out by Scoutmasters at Darussalam Islamic Boarding School Bogor. This study aims to determine how the strategy of character building for students through scout extracurricular activities at Darussalam Islamic Boarding School Bogor. The data collection techniques in this study are observation, interviews, and documentation. The validity of the data was obtained from the triangulation technique which was achieved by comparing the observed data with the interview data. The data analysis technique in this study has 3 stages, namely data collection, data presentation, and with conclusion. The results of the study indicate that habituation, example, assignments, lectures, and punishments or sanctions are methods used in fostering the character of students through scouting activities. Habituation by telling students to come on time, greet each other, perform congregational prayers and others. Exemplary is to provide examples of direct actions to students. Assignment is when the inauguration activity takes place, new students are given individual and group assignments. Lecture by providing an explanation of the importance of good morals as exemplified by the Prophet Muhammad. Penalties or sanctions for students who violate the rules in the form of a direct warning by the coach, asked to read the Dasa Dharma in front of other students, run in the field. And what causes students to experience boredom, boredom, truant during scouting practice is due to the density of activities on Thursday. The types of scouting activities are routine training, skills, General Skill Requirements (SKU), Marching Skill Practice (PBB), Special Skill Mark (TKK), Resume and Evaluation. The values ​​that are instilled include religious, discipline, independence, responsibility, environmental care, leadership and tolerance.